Pengaruh Pengembangan Karyawan. Lingkungan Kerja dan Komunikasi terhadap Semangat Kerja Karyawan pada Kantor Pos Lhokseumawe - Likdanawati Likdanawati; Hamdiah Hamdiah (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
This study aims to examine the Effect of Employee Development, Work Environment, and Communication on the spirit at work of employees at the Postal Office of Lhokseumawe. This study uses primary data obtained by distributing questionnaires to all respondents. The research samples are 55 respondents selected using the Probability sampling technique. The data analysis method used is multiple linear regression analysis with the help of SPSS. The results show that Employee Development has a significant effect on the spirit at work of employees at the Postal Office of Lhokseumawe, the Work Environment has a significant effect on the spirit at work of employees at the Postal Office of Lhokseumawe, and Communication has a significant effect on the spirit at work of employees at the Postal Office of Lhokseumawe. Employee Development, Work Environment, and Communication affect the spirit at work of employees at the Postal Office of Lhokseumawe.Keywords: Employee Development, Work Environment,Communication, Moral Spirit.